2010
DOI: 10.1039/c0lc00185f
|View full text |Cite
|
Sign up to set email alerts
|

Sorted cell microarrays as platforms for high-content informational bioassays

Abstract: We report on surface-engineered microarrays that provide in situ cell sorting, localization, and immobilization of various subsets of human primary lymphocytes, followed by an on-chip bioassay for ionizing-radiation-induced cytogenetic damage. The microarray format eliminates the necessity of separating cell sub-populations by alternative means (such as fluorescence- or magnetic-activated cell sorting) prior to performing informational bioassays. To exemplify the potential of this on-chip cytometry approach, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…Microarrays of HR1K Burkitt's lymphoma cells (B cells) and Jurkat cells (T cells) were generated by capturing the cells on microarray surfaces that display spots of immobilized anti-CD45 antibody ( Supplementary Fig. 2) [26][27][28] . It is noteworthy that both cell types express the antigen CD45.…”
Section: Resultsmentioning
confidence: 99%
“…Microarrays of HR1K Burkitt's lymphoma cells (B cells) and Jurkat cells (T cells) were generated by capturing the cells on microarray surfaces that display spots of immobilized anti-CD45 antibody ( Supplementary Fig. 2) [26][27][28] . It is noteworthy that both cell types express the antigen CD45.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers assessed cell radio-sensitivity by examining the level of apoptosis, they realized that it depends not only on dose value, but also on post-exposure elapsed time. [2934] Some studies have suggested time-dependent expression,[16] particularly in the first 5 hours and a return to the base-line within 20 hours. [35] But, in our study, these changes remained for a much long time and gradually faded over a week.…”
Section: Resultsmentioning
confidence: 99%
“…[12131415] In some studies, performed on lymphocytes suggest gene expression level are time-dependent. [16] A good knowledge of post-irradiation history of a biomarker would help to assess absorbed dose, regardless of the elapsed time between exposure and sampling. In vitro studies, mostly have been carried out on peripheral blood lymphocytes (PBL), and the elapsed time between irradiation and gene expression assessment varies from 15 minutes to 72 hours.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Polymer microarrays have become a key tool for materials discovery projects and have been widely used to assess a number of material-biological applications including stem cells, [11][12][13] bacteria, [14][15][16] and cell sorting. [17][18][19][20] The large number of material interactions that can be rapidly assessed using polymer microarrays has resulted in surface structure-property models that describe the biological performance of materials based upon a measured physical property. To achieve this, high throughput surface characterization of polymer microarrays has been a necessary development and has been achieved for various techniques including x-ray photoelectron spectroscopy, ToF-SIMS 8,9 water contact angle (WCA) 21,22 atomic force microscopy, 23 surface plasmon resonance, 24 and force measurements.…”
Section: Introductionmentioning
confidence: 99%